FRACTURE PATTERN AND STRESS ANALYSIS BASED ON BOREHOLE IMAGES AND SEISMIC ATTRIBUTES - BIN MOHAMMAD, MUHAMMAD HANIF HAZIQ (Universiti Teknologi PETRONAS, 2014)
Since fracture behaviour tends to be localized, integration of borehole image and seismic attributes is believed to decrease the uncertainty in characterizing high fracture density areas. The project objective is to delineate the fracture pattern trends using borehole images and seismic attributes in the fractured basement of the Anding field. The metasediments of Tanjung Kempit is chosen as the onshore analogue as certain researchers believe them to represent uplifted basement rocks of Peninsular Malaysia. In the onshore analogue, azimuth and dip of the major highly dipping conjugate fractures and minor gently dipping tensile fractures were measured and analysed. It is believed that the area underwent two phases of an E-W compressional and a transpressional event which folded the formation forming the conjugate and tensile fractures. Seismic interpretation of faults and top of basement structure was done. Interpretation of fractures and foliation in FMI data of Well X and Well Y was done and the high fracture density areas were correlated with the ant tracking cube and amplitude cube generated from the seismic. Fractures were extracted from the ant track cube and their azimuth and dips were compared with the FMI interpretation and onshore analogue. The highly dipping fractures (>50°) in the seismic are fault associated fractures as they have major WNW-ESE azimuth similar to the interpreted faults. The gently dipping fractures (<50°) are sheet fractures as they also have NW-SE orientation similar to the foliation/bedding measured from FMI and also the bedding of the onshore analogue. The onshore analogue fractures couldn’t be correlated well with the offshore data due to differences in age, lithology and less focus on fault associated fractures.